Analyzing sediment characteristics between intertidal and supratidal zones at Kelapa Kunjir Beach, Lampung Indonesia - Delilla Suhanda; Mohammad Ashari Dwiputra (Fakultas Sains Institut Teknologi Sumatera, 2025)
The differing hydrodynamic processes between the intertidal and supratidal zones significantly influence the distribution of grain size and sediment types. This study aims to analyze the sediment fractions and types based on granulometric parameters in both zones. The method involved collecting sediment samples from five stations in each zone, followed by dry sieving laboratory analysis and granulometric statistical calculations. The results show that the intertidal zone is dominated by gravelly sand, with gravel ranging from 20.4% to 35.5% and sand from 61.3% to 78.7%, with no silt or clay detected. The supratidal zone exhibited more variation, with gravel ranging from 16.4% to 38.2%, sand from 41.3% to 70.6%, and silt from 2.3% to 39.2%. Sorting values ranged from 1.5 to 2.3, skewness from −0.8 to −0.07, and kurtosis between 1.7 and 4.0. Sediment types in the intertidal zone were predominantly gravelly sand, while the supratidal zone consisted of gravelly mud and muddy sand. It is concluded that differences grain size distribution and sediment types between the two zones are influenced by variations in environmental energy. The intertidal zone reflects moderate to high-energy conditions, while the supratidal zone indicates a lower-energy environment with potential for fine material accumulation.